Formulations and Antibacterial Activity of Shallot (Allium cepa L.) Peel Extract Patch against Streptococcus pyogenes - Siwi Nur Azizah; Luay Banna Ste; Khansa Syahira Maulida; Nadrah Adinda Zahirah; Salsabila Naura Nisa; Sri Mulyaningsih; Dewa Ayu Arimurni; Citra Ariani Edityaningrum (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Bacterial pharyngitis is an inflammatory condition in the back of the throat caused by Streptococcus pyogenes. Patients are often prescribed antibiotics and antiinflammatories to alleviate pain and discomfort while reducing bacterial growth in the throat. However improper and prolonged use of antibacterial and antiinflammatory agents increases the risk of bacterial resistance and side effects. An often discarded Shallot (Allium cepa L.) peel rich in flavonoids with great antibacterial and anti-inflammatory properties is potentially used as an alternative treatment for bacterial pharyngitis. Objective: This study aimed to develop shallot peel extract as an antibacterial against Streptococcus pyogenes. Methods: Patch was formulated with variations in extract concentration of 5% (F1), 10% (F2), and 15% (F3) to observe their influence on weight uniformity, thickness, folding endurance, surface pH, moisture content, and antibacterial activity using disc diffusion. Results: All formulations produce slightly heavy and thicker but uniform patches (CV<5%), surface pH suitable for application in the skin (4.6-4.9), flexible and durable patches with high folding endurance (> 300 folds), good moisture content (<10%) and moderate to strong antibacterial activity (inhibition zone diameter ranging from 9 to 13.67 mm). Variations in extract concentration in the formula significantly influenced the thickness, weight, folding endurance, and also the antibacterial activity of the patches. Higher concentrations of extract produce thicker and heavier patches but stronger antibacterial activity against pharyngitis pathogens. Conclusion: Therefore, antibacterial patches containing up to 15% shallot peel extract are potentially used as an alternative treatment for pharyngitis.